Welfare assessment of dromedary camels kept under pastoralism in Pakistan - Padalino, Barbara; Faraz, Asim; Masebo, Naod Thomas; Waheed, Abdul; Ishaq, Hafiz Muhammad; Tauqir, Nasir Ali; Abbasi, Ali Raza; Menchetti, Laura (Frontiers in Veterinary Science, 2024)
Standardized welfare assessment protocols are crucial to enhance animal welfare; up to date, there is no data on the level of welfare of camels kept under pastoralism. A tailored protocol for measuring welfare in dromedary camels kept under nomadic pastoralist conditions was recently developed, drawing from the currently available welfare protocol for dromedary camels kept in intensive systems. This study, therefore, aimed to apply the newly developed tailored protocol and assess the welfare of dromedary camels kept under pastoralism in the Southern Punjab Province of Pakistan. A total of 44 welfare indicators (animal-, resource, and management-based measures) aligning with animal welfare principles (“Good Feeding”, “Good Housing”, “Good Health”, and “Appropriate Behavior”) were gathered into two assessment levels: “Caretaker-Herd level” and “Animal level”. Data were collected in 2023 in the Cholistan desert in the southern Punjab province. Fifty-four herds were evaluated for a total population of 1,186 camels, of which 510 (495 females and 15 males; average age: 5–6 years old) were assessed at the animal level. The indicators were scored and aggregated to obtain Principle Aggregated Indexes (PAIs) and a total Welfare Index (TWI). Using the PAIs classification, 4 herds were categorized as excellent, 42 satisfactory, and 8 unsatisfactory. Total Welfare Index (TWI) varied from 55.7 to 82.2, and the thresholds for classification into tertiles were 65.4 and 70.6. Good feeding and Good housing were the most problematic PAIs, with Good feeding as the most influential variable for classification into welfare categories. As expected, camels kept under pastoralism had a higher level of welfare than those reported in the literature for intensive systems, especially concerning the Appropriate Behavior principle. Our findings are a first step in proposing welfare standards for dromedary in Pakistan and worldwide.